The gene for the heat-shock protein 70 of Euplotes focardii, an Antarctic psychrophilic ciliate - La Terza, Antonietta; Miceli, Cristina; Luporini, Pierangelo (Antarctic Science, 2004)
In the Antarctic ciliate, Euplotes focardii, the heat-shock protein 70 (Hsp70) gene does not show any appreciable activation by a thermal stress. Yet, it is activated to appreciable transcriptional levels by oxidative and chemical stresses, thus implying that it evolved a mechanism of selective, stress-specific response. A basic step in investigating this mechanism is the determination of the complete nucleotide sequence of the E. focardii Hsp70 gene. This gene contains a coding region specific for an Hsp70 protein that carries unique amino acid substitutions of potential significance for cold adaptation, and a 5′ regulatory region that includes sequence motifs denoting two distinct types of stress-inducible promoters, known as "Heat Shock Elements" (HSE) and "Stress Response Elements" (StRE). From the study of the interactions of these regulatory elements with their specific transactivator factors we expect to shed light on the adaptive modifications that prevent the Hsp70 gene of E. focardii from responding to thermal stress while being responsive to other stresses.